2016
DOI: 10.1088/0963-0252/25/3/035014
|View full text |Cite
|
Sign up to set email alerts
|

A 3D model of a reverse vortex flow gliding arc reactor

Abstract: In this computational study, a gliding arc plasma reactor with a reverse-vortex flow stabilization is modelled for the first time by means of a fluid plasma description. The plasma reactor is operating with argon gas at atmospheric pressure. The gas flow is simulated using the kε RANS turbulent model. A quasi-neutral fluid plasma model is employed for computing the plasma properties. The plasma arc movement in the reactor is observed, and the results for the gas flow, electrical characteristics, plasma density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(118 citation statements)
references
References 25 publications
6
111
1
Order By: Relevance
“…We are currently investigating the gas flow dynamics by 2D and 3D fluid dynamics modeling [80,81] and will elaborate on these resultsint he future by particle tracings imulations. However,t he conversion needs to be further improved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We are currently investigating the gas flow dynamics by 2D and 3D fluid dynamics modeling [80,81] and will elaborate on these resultsint he future by particle tracings imulations. However,t he conversion needs to be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the gas temperature can be calculated in the model( Supporting Information), but in this study we assume certain values based on 3D fluid dynamics simulations [80,81] and reported data. [82] Indeed, to obtain realistic calculations with this 0D model, we would need more accurated ata on the energy released by some chemical reactions and on the effect of vibration-translation relaxation of the CO 2 vibrational levels upon collision with CH 4 ;t hesed ata were not availablei nt he literature.…”
Section: Calculated Plasmac Haracteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A considerable number of experiments have been conducted to study the slip velocity and column length, the dynamic behavior, and the electrical characterization . Apart from the experimental studies, several theoretical studies have also been performed . They are motivated by the need of a more profound understanding of the discharge operation, which is very difficult to be achieved with experimental methods, due to the complexity of the discharge – non‐stationary behavior, complex plasma, etc.…”
Section: Introductionmentioning
confidence: 99%